2021
DOI: 10.1002/jobm.202100288
|View full text |Cite
|
Sign up to set email alerts
|

N‐([1,1ʹ‐biaryl]‐4‐yl)‐1‐naphthamide‐based scaffolds synthesis, their cheminformatics analyses, and screening as bacterial biofilm inhibitor

Abstract: Naphthamides have pharmacological potential as they express strong activities against microorganisms. The commercially available naphthoyl chloride and 4-bromoaniline were condensed in dry dichloromethane (DCM) in the presence of Et 3 N to form N-(4-bromophenyl)-1-naphthamide (86%) (3). Using a Pd(0) catalyzed Suzuki-Miyaura Cross-Coupling reaction of (3) and various boronic acids, a series of N-([1,1ʹ-biaryl]-4-yl)-1-naphthamide derivatives (4a-h) were synthesized in moderate to good yields. The synthesized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Amides simultaneously kill bacteria or cause stagnant growth and have a positive inhibitory impact. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Amides simultaneously kill bacteria or cause stagnant growth and have a positive inhibitory impact. 42 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the amides behave as a hydrophilic binding site against bacterial enzyme proteins, which may cause death or make static growth, leading to good inhibitory activity. 36 Further, we studied the N, O, and S heterocycles carboxamides like N-(4-bromophenyl)furan-2-carboxamide, 32 2-aryl-4-chlorophenyl-5-arylthiophene-2-carboxylates 34 4-bromo-N-(5-methyl-1H-pyrazol-3-yl) benzamide, 35 N-(4-methylpyridin-2-yl) Thiophene-2-Carboxamide 37 to study the effectiveness of these scaffolds and found effectiveness against different resistant strains of E. coli, A. baumannii, S. enterica, E. cloacae, S. aureus and K. pneumoniae. We found that heterocyclic carboxamides are pivotal in anti-bacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking studies were accomplished to identify the stable interactions of synthesized compounds (3b, 3c, 3d, 3e, 3h) against E. coli curli fiber biogenesis biofilm receptor protein using Auto Dock Tools version 1.5.6 (ADT) software [47]. The dataset of compounds was categorized into three activity levels: highly active (3e), moderately active (3c, 3h), and least active (3b, 3d).…”
Section: Molecular Docking Studymentioning
confidence: 99%